MoS2-based nano composite film as well as preparation method, application and device thereof

By introducing the Ti transition layer and the MoS2 nanocomposite layer co-doped with Ti and C into the MoS2 film, a nanocomposite structure is formed, which solves the problem of tribological performance degradation of MoS2 film in complex environments, and realizes the temperature of vacuum and atmospheric room temperature Good lubricating performance in high temperature environments meets the reliability requirements of aerospace applications.

CN119121126AActive Publication Date: 2024-12-13LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411261290.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The deterioration of tribological properties of MoS2 films in complex aerospace environments leads to a reduced life and reliability of the moving mechanism, limiting its application range, especially in the vacuum, atmospheric room temperature and high temperature environments.

Method used

Using Ti transition layer and MoS2 nanocomposite layer co-doped with Ti and C, MoS2 nanocomposite film is deposited on the substrate surface through magnetron sputtering technology to form a nanocomposite structure that enhances the film-based binding force, combining the vacuum friction characteristics of MoS2. , the atmospheric friction characteristics of C and the strengthening effect of Ti, improve the environmental adaptability and antioxidant properties of the film.

Benefits of technology

It has good tribological properties under vacuum, atmospheric room temperature and high temperature (500℃) environments, significantly improving the hardness and elastic modulus of the film, enhancing the barrier ability to water and oxygen molecules, and meeting the reusable aerospace Reliable lubrication and service requirements of aircraft in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121126A_ABST
    Figure CN119121126A_ABST
Patent Text Reader

Abstract

The invention provides a MoS2-based nano composite film and a preparation method, application and device thereof, and belongs to the technical field of surface engineering.The MoS2-based nano composite film comprises a Ti transition layer and a Ti and C co-doped MoS2 nano composite layer deposited on the surface of the Ti transition layer; in the Ti and C co-doped MoS2 nano composite layer, the percentage of the number of Ti atoms is 5.0 to 8.0 percent, the percentage of the number of C atoms is 35.0 to 45.0 percent, and the balance is MoS2. The MoS2-based nano composite film provided by the invention has good mechanical properties, also has good tribological properties in vacuum, atmospheric normal temperature and high temperature (500 DEG C) environments, and shows excellent environmental adaptive ability and oxidation resistance; reliable lubrication and service requirements of reusable aerospace aircrafts in complex environments can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of surface engineering and specifically relates to a MoS 2 Based nano-composite film and its preparation method, application and device. Background Art

[0002] MoS 2 It is widely used in the aerospace field due to its excellent vacuum lubrication performance. 2 The lubrication properties of stainless steel come from its hexagonal layered crystal structure, in which the layers are bonded by weak van der Waals forces, so the shear strength is low and interlayer slip easily occurs under the action of friction.

[0003] In recent years, the development of reusable space transportation systems has been in full swing under the leadership of SpaceX in the United States. The life cycle of this transportation system traverses different service environments such as ground assembly and storage, leaving the atmosphere, entering orbit, reentering the atmosphere and returning to the ground. The environment involved in the reusable space transportation system includes normal atmospheric temperature, high atmospheric temperature and vacuum. 2 As an important component of aerospace motion mechanisms, thin films need to provide reliable lubrication performance in various environments. However, the complex and changing environment brings severe challenges to it.

[0004] Usually MoS 2 The film is only suitable for non-reactive environments such as vacuum and inert atmosphere. Once exposed to the atmosphere, the interaction with water molecules and oxygen will cause its friction coefficient and wear rate to increase significantly. In addition, in an atmospheric high temperature environment above 300°C, MoS 2 It will be rapidly oxidized to MoO 3 , the change of film chemical composition will lead to the increase of friction and wear. 2 The degradation of the tribological properties of thin films will have serious adverse effects on the life and reliability of motion mechanisms, greatly limiting their application scope in the aerospace field.

[0005] Atmospheric high temperature MoS disclosed in Chinese patent CN 111621745 B 2 The thin film system will MoS 2 The use temperature of the film has been raised to 400°C. However, the complex service environment of the reusable space transportation system requires MoS 2 The thin film system can also achieve reliable lubrication in a vacuum environment. On the other hand, the service environment threshold of the thin film needs to be increased as much as possible.

[0006] Therefore, designing new MoS 2The base film can achieve reliable lubrication of the film in multiple environments of vacuum, normal atmospheric temperature and high temperature, which has important application value and practical significance for the development of reusable space transportation systems and ensuring the safe service of moving mechanisms. Summary of the invention

[0007] In view of this, the object of the present invention is to provide a MoS 2 Based on nanocomposite film and preparation method, application and device thereof. The MoS provided by the present invention 2 The nanocomposite film has good tribological properties in vacuum, normal atmospheric temperature and high temperature (500℃) environments.

[0008] In order to achieve the above object, the present invention provides the following scheme:

[0009] The present invention provides a MoS 2 A nanocomposite film comprising a Ti transition layer and Ti and C co-doped MoS deposited on the surface of the Ti transition layer. 2 Nanocomposite layer; the Ti and C co-doped MoS 2 In the nanocomposite layer, the percentage of Ti atoms is 5.0-8.0%, the percentage of C atoms is 35.0-45.0%, and the balance is MoS 2 .

[0010] Preferably, the thickness of the Ti transition layer is 100 to 300 nm; 2 The thickness of the nanocomposite film is 2.0 to 3.0 μm.

[0011] Preferably, the MoS 2 The hardness of the nanocomposite film is greater than 8.0 GPa, the elastic modulus is greater than 90.0 GPa, the average friction coefficient in vacuum is less than 0.05, the average friction coefficient in normal atmospheric temperature is less than 0.11, and the average friction coefficient in atmospheric high temperature of 500° C. is less than 0.1.

[0012] The present invention provides the MoS 2 The method for preparing a nano-composite film comprises the following steps:

[0013] Using a first argon gas as a working gas and a first Ti target material for first magnetron sputtering, while first heating the substrate and applying a negative bias voltage, a Ti transition layer is deposited on the surface of the substrate to obtain a Ti transition layer deposited substrate; the magnetron sputtering current of the first Ti target material is 400-800 mA, and the first magnetron sputtering time is 10-30 min;

[0014] Using the second argon as the working gas, MoS 2The target material, the second Ti target material and the C target material are simultaneously subjected to a second magnetron sputtering, and the substrate for depositing the Ti transition layer is simultaneously subjected to a second heating to deposit Ti and C co-doped MoS on the surface of the Ti transition layer. 2 Nanocomposite layer, to obtain the MoS 2 Based nanocomposite films;

[0015] The MoS 2 The magnetron sputtering power of the target material is 200-300W, the magnetron sputtering power of the C target material is 200-300W, the magnetron sputtering current of the second Ti target material is 80-120mA, and the time of the second magnetron sputtering is 3.5-5.0h.

[0016] Preferably, the flow rate of the first argon gas is 20-40 sccm, and the pressure is 0.5-0.8 Pa; the temperature of the first heating is 100-200° C., and the negative bias voltage is -100-0V.

[0017] Preferably, the flow rate of the second argon gas is 20-40 sccm, and the pressure is 0.5-0.8 Pa; the temperature of the second heating is 100-200° C., and no substrate bias is applied.

[0018] Preferably, the material of the matrix includes Si, W18Cr4V, Inconel 718 or 440C.

[0019] Preferably, before the first magnetron sputtering, the substrate is ultrasonically cleaned and plasma cleaned in sequence, and the target material is pre-sputtered.

[0020] The present invention provides the MoS 2 The MoS prepared by the preparation method of the above-mentioned scheme 2 Application of nanocomposite films in surface engineering of aerospace mechanical moving parts.

[0021] The present invention provides a device, comprising a substrate and MoS deposited on the surface of the substrate. 2 Based nanocomposite film; the MoS 2 The nanocomposite film is the MoS 2 The MoS prepared by the preparation method of the above-mentioned scheme 2 Nanocomposite thin films.

[0022] The present invention provides a MoS 2 The nanocomposite film comprises a Ti transition layer and Ti and C co-doped MoS deposited on the surface of the Ti transition layer. 2 Nanocomposite layer; the Ti and C co-doped MoS 2In the nanocomposite layer, the percentage of Ti atoms is 5.0-8.0%, the percentage of C atoms is 35.0-45.0%, and the balance is MoS 2 The MoS provided by the present invention 2 The nanocomposite film system includes a Ti transition layer to enhance the bonding strength between the film and the substrate, a Ti and C co-doped MoS 2 Nanocomposite layer, the system couples MoS 2 The vacuum friction characteristics of MoS, the atmospheric friction characteristics of C and the strengthening effect of Ti have greatly improved the 2 The environmental adaptability of the film. The MoS 2 The nanocomposite structure of the nanocomposite film can inhibit the 2 The rapid growth of the grains in a columnar manner increases the density of the film system, improves the mechanical properties of the film such as hardness and elastic modulus, and the nanocomposite structure can enhance the barrier ability to water and oxygen molecules, passivating MoS 2 The active sites at the grain interface improve the anti-oxidation performance of the film. 2 The nanocomposite film has good mechanical properties, as well as good tribological properties in vacuum, normal atmospheric temperature and high temperature (500°C) environments, showing excellent environmental adaptability and anti-oxidation properties, and can meet the reliable lubrication and service requirements of reusable aerospace vehicles in complex environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 The Ti and C co-doped MoS obtained in Example 1 of the present invention 2 SEM images of the surface morphology of the nanocomposite layer;

[0025] Figure 2 The MoS prepared in Example 1 of the present invention 2 Scanning electron microscope image of the cross-sectional morphology of the nanocomposite film;

[0026] Figure 3 The MoS prepared in Example 1 of the present invention 2 Transmission electron microscopy image of the nanocomposite film;

[0027] Figure 4 The MoS prepared in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention is2 Friction curve of nanocomposite film in vacuum at room temperature;

[0028] Figure 5 The MoS prepared in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention is 2 Friction curve of nanocomposite film at room temperature;

[0029] Figure 6 The MoS prepared in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present invention is 2 Friction curve of the nanocomposite film based on MgO in high atmospheric temperature (500℃). DETAILED DESCRIPTION

[0030] The present invention provides a MoS 2 A nanocomposite film comprising a Ti transition layer and Ti and C co-doped MoS deposited on the surface of the Ti transition layer. 2 Nanocomposite layer; the Ti and C co-doped MoS 2 In the nanocomposite layer, the percentage of Ti atoms is 5.0-8.0%, the percentage of C atoms is 35.0-45.0%, and the balance is MoS 2 .

[0031] In the present invention, the thickness of the Ti transition layer is preferably 100 to 300 nm, more preferably 120 to 260 nm, and more preferably 150 to 240 nm; 2 The thickness of the nanocomposite film is 2.0 to 3.0 μm, more preferably 2.2 to 2.8 μm.

[0032] In the present invention, the Ti and C co-doped MoS 2 In the nanocomposite layer, the percentage of Ti atoms is 4.0-9.0%, more preferably 5.0-8.0%; the percentage of C atoms is 35.0-45.0%, more preferably 38-42%, and the remainder is MoS 2 .

[0033] In the present invention, the MoS 2The hardness of the nanocomposite film is preferably >8.0GPa, the elastic modulus is preferably >90.0GPa, the average friction coefficient in vacuum is preferably <0.05, more preferably 0.01≤average friction coefficient <0.05, the average friction coefficient in atmospheric normal temperature is preferably <0.11, more preferably 0.06-0.1, the average friction coefficient at atmospheric high temperature 500°C is preferably <0.1, more preferably 0.05≤average friction coefficient <0.1. In the present invention, the temperature under atmospheric normal temperature environment is preferably 18-30°C, more preferably 20-25°C; the humidity under atmospheric normal temperature environment is preferably 30-50%RH, more preferably 37-43%RH.

[0034] The MoS provided by the present invention 2 The nanocomposite film system includes a Ti transition layer to enhance the bonding strength between the film and the substrate, a Ti and C co-doped MoS 2 Nanocomposite layer, the system couples MoS 2 The vacuum friction characteristics of MoS, the atmospheric friction characteristics of C and the strengthening effect of Ti have greatly improved the 2 The environmental adaptability of the film. The MoS 2 The nanocomposite structure of the nanocomposite film can inhibit the 2 The rapid growth of the grains in a columnar manner increases the density of the film system, improves the mechanical properties of the film such as hardness and elastic modulus, and the nanocomposite structure can enhance the barrier ability to water and oxygen molecules, passivating MoS 2 The active sites at the grain interface improve the anti-oxidation performance of the film. 2 The nanocomposite film has good mechanical properties, as well as good tribological properties in vacuum, normal atmospheric temperature and high temperature (500°C) environments, showing excellent environmental adaptability and anti-oxidation properties, and can meet the reliable lubrication and service requirements of reusable aerospace vehicles in complex environments.

[0035] The present invention provides the MoS 2 The method for preparing a nano-composite film comprises the following steps:

[0036] Using a first argon gas as a working gas and a first Ti target material for first magnetron sputtering, while first heating the substrate and applying a negative bias voltage, a Ti transition layer is deposited on the surface of the substrate to obtain a Ti transition layer deposited substrate; the magnetron sputtering current of the first Ti target material is 400-800 mA, and the first magnetron sputtering time is 10-30 min;

[0037] Using the second argon as the working gas, MoS 2The target material, the second Ti target material and the C target material are simultaneously subjected to a second magnetron sputtering, and the substrate for depositing the Ti transition layer is simultaneously subjected to a second heating to deposit Ti and C co-doped MoS on the surface of the Ti transition layer. 2 Nanocomposite layer, to obtain the MoS 2 Based nanocomposite films;

[0038] The MoS 2 The magnetron sputtering power of the target material is 200-300W, the magnetron sputtering power of the C target material is 200-300W, the magnetron sputtering current of the second Ti target material is 80-120mA, and the time of the second magnetron sputtering is 3.5-5.0h.

[0039] The present invention uses a first argon gas as a working gas, performs a first magnetron sputtering on a first Ti target material, and simultaneously performs a first heating on a substrate and applies a negative bias voltage, depositing a Ti transition layer on the surface of the substrate to obtain a Ti transition layer deposited substrate.

[0040] Before the first magnetron sputtering, the present invention also preferably includes sequentially performing ultrasonic cleaning and plasma cleaning on the substrate, and pre-sputtering on the target material.

[0041] In the present invention, the ultrasonic cleaning preferably comprises placing the substrate in petroleum ether and anhydrous ethanol in sequence and ultrasonic cleaning each for 20 minutes.

[0042] In the present invention, the plasma cleaning preferably includes: pumping the pressure of the magnetron sputtering chamber to 1.0×10 -3 Pa, a bias voltage of -500 to -300 V is applied to the substrate, the substrate temperature is 100 to 200° C., and plasma cleaning is performed for 10 to 20 minutes. In the present invention, the difference in bias voltage during the cleaning stage will not affect the performance of the final film.

[0043] In the present invention, the pre-sputtering time is preferably 10 minutes. The present invention has no special requirements for the pre-sputtering, and any method known in the art can be used.

[0044] In the present invention, the material of the substrate preferably includes Si, W18Cr4V, Inconel 718 or 440C.

[0045] In the present invention, the magnetron sputtering current of the first Ti target is preferably 400-800 mA, more preferably 500-700 mA, and more preferably 550-650 mA; the first magnetron sputtering time is preferably 10-30 min, and more preferably 15-25 min.

[0046] In the present invention, the flow rate of the first argon gas is preferably 20 to 40 sccm, more preferably 25 to 35 sccm; the pressure of the first argon gas is preferably 0.5 to 0.8 Pa, more preferably 0.6 to 0.7 Pa; the temperature of the first heating is preferably 100 to 200°C, more preferably 120 to 260°C, more preferably 150 to 240°C; the negative bias voltage is preferably -100 to 0 V, more preferably -80 to -40 V, more preferably -60 to -45 V. In the present invention, it is preferred to use a DC power supply current mode to magnetron sputter the first Ti target.

[0047] The Ti transition layer substrate is obtained by using the second argon gas as the working gas to deposit MoS 2 The target material, the second Ti target material and the C target material are simultaneously subjected to a second magnetron sputtering, and the substrate for depositing the Ti transition layer is simultaneously subjected to a second heating to deposit Ti and C co-doped MoS on the surface of the Ti transition layer. 2 Nanocomposite layer, to obtain the MoS 2 Nanocomposite thin films.

[0048] In the present invention, the flow rate of the second argon gas is 20 to 40 sccm, and more preferably 25 to 35 sccm; the pressure of the second argon gas is preferably 0.5 to 0.8 Pa, and more preferably 0.6 to 0.7 Pa; the temperature of the second heating is preferably 100 to 200°C, and more preferably 120 to 260°C, and more preferably 150 to 240°C, and no substrate bias is applied.

[0049] In the present invention, the MoS 2 The magnetron sputtering power of the target is preferably 200-300W, more preferably 230-280W; the magnetron sputtering power of the C target is preferably 200-300W, more preferably 230-280W; the magnetron sputtering current of the second Ti target is preferably 80-120mA, more preferably 90-115mA; the second magnetron sputtering time is preferably 3.5-5.0h, more preferably 3.7-4.5h. In the present invention, it is preferred to use a radio frequency power supply to sputter the MoS 2 The target and the C target are magnetron sputtered, and the second Ti target is sputtered using a DC power supply current mode.

[0050] The present invention provides the MoS 2 The MoS prepared by the preparation method of the above-mentioned scheme 2 Application of nanocomposite films in surface engineering of aerospace mechanical moving parts.

[0051] The present invention provides a device, comprising a substrate and MoS deposited on the surface of the substrate. 2 Based nanocomposite film; the MoS 2 The nanocomposite film is the MoS 2 The MoS prepared by the preparation method of the above-mentioned scheme 2 Nanocomposite thin films.

[0052] In the present invention, the material of the substrate preferably includes Si, W18Cr4V, Inconel 718 or 440C.

[0053] The present invention provides application of the device described in the above scheme in surface engineering of moving parts of aerospace machinery.

[0054] In order to further illustrate the present invention, a MoS 2 The nanocomposite film and its preparation method, application and device are described in detail, but they should not be understood as limiting the scope of protection of the present invention.

[0055] Example 1

[0056] Preparation of MoS on the surface of Si matrix material 2 The nanocomposite film is prepared by the following specific steps:

[0057] The substrate material Si was ultrasonically cleaned in petroleum ether and anhydrous ethanol for 20 min each, and then wiped clean with a dust-free cloth; the ultrasonically cleaned substrate was placed in a magnetron sputtering chamber and vacuumed until the pressure was less than 1.0×10 -3 Pa, turn on the sample tray heating to keep the substrate temperature at about 150°C, then apply a -300V bias voltage to the substrate for cleaning, and the cleaning time is 20 minutes; after the sample is cleaned, pre-sputter all the targets, and the pre-sputtering cleaning time is 10 minutes;

[0058] Then, high-purity argon gas was filled into the magnetron sputtering chamber as the working gas. 2 Target (purity 99.99%), Ti target (purity 99.995%) and C target (purity 99.999%) are used as sputtering targets. The specific steps are as follows:

[0059] Depositing a Ti transition layer, magnetron sputtering a Ti target, heating the pre-sputtered substrate and applying a negative bias voltage, depositing a Ti transition layer on the surface of the substrate, and obtaining a deposited Ti transition layer substrate; the Ti target magnetron sputtering current is 500 mA, the working gas flow rate is 40 sccm, the magnetron sputtering pressure is 0.65 Pa, the substrate temperature is 150° C., the substrate bias voltage is -60 V, and the magnetron sputtering time is 30 min;

[0060] Deposition of Ti and C co-doped MoS 2 Nanocomposite layer, MoS 2 The target material, the Ti target material and the C target material are magnetron sputtered simultaneously, and the substrate for depositing the Ti transition layer is heated at the same time, and Ti and C co-doped MoS are deposited on the surface of the Ti transition layer. 2 Nanocomposite layer, to obtain the MoS 2 Based nanocomposite film; MoS 2 The target magnetron sputtering power is 250W, the C target magnetron sputtering power is 250W, the Ti target magnetron sputtering current is 110mA, the working gas flow rate is 40sccm, the magnetron sputtering pressure is 0.65Pa, the substrate temperature is 150℃, there is no bias, and the deposition time is 4.0h.

[0061] Example 2

[0062] Preparation of MoS on the surface of W18Cr4V steel block 2 The nanocomposite film is prepared by the following specific steps:

[0063] The W18Cr4V steel block was ultrasonically cleaned in petroleum ether and anhydrous ethanol for 20 min each, and then wiped clean with a dust-free cloth. The ultrasonically cleaned substrate was placed in a magnetron sputtering chamber and vacuumed until the pressure was less than 1.0×10 - 3 Pa, turn on the sample tray heating to keep the substrate temperature at about 150°C, then apply a -500V bias voltage to the substrate for cleaning, and the cleaning time is 20 minutes; after the sample is cleaned, pre-sputter all the target materials, and the pre-sputtering cleaning time is 10 minutes;

[0064] Then, high-purity argon gas was filled into the magnetron sputtering chamber as the working gas. 2 Target (purity 99.99%), Ti target (purity 99.995%) and C target (purity 99.999%) are used as sputtering targets. The specific steps are as follows:

[0065] Depositing a Ti transition layer, magnetron sputtering a Ti target, heating the pre-sputtered substrate and applying a negative bias voltage, depositing a Ti transition layer on the surface of the substrate, and obtaining a deposited Ti transition layer substrate; the magnetron sputtering current of the Ti target is 500 mA, the working gas flow rate is 40 sccm, the magnetron sputtering pressure is 0.65 Pa, the substrate temperature is 150° C., the substrate bias voltage is -60 V, and the sputtering time is 30 min;

[0066] Deposition of Ti and C co-doped MoS 2 Nanocomposite layer, MoS 2The target material, the Ti target material and the C target material are magnetron sputtered simultaneously, and the substrate for depositing the Ti transition layer is heated at the same time, and Ti and C co-doped MoS are deposited on the surface of the Ti transition layer. 2 Nanocomposite layer, to obtain the MoS 2 Based nanocomposite film; MoS 2 The target magnetron sputtering power is 250W, the C target magnetron sputtering power is 250W, the Ti target magnetron sputtering current is 110mA, the working gas flow rate is 40sccm, the sputtering pressure is 0.65Pa, the substrate temperature is 150℃, there is no bias, and the deposition time is 4.0h.

[0067] Comparative Example 1

[0068] This comparative example is a method for preparing a Mo-S-Ti nanocomposite film without doping with C element, and the specific steps are as follows:

[0069] Si and W18Cr4V were selected as matrix materials, where the matrix Si was used to characterize the elemental composition and mechanical properties of the film, and the matrix W18Cr4V was used to characterize the tribological properties of the film under different test environments. The matrix materials were ultrasonically cleaned in petroleum ether and anhydrous ethanol for 20 min each, and then wiped clean with a dust-free cloth. The ultrasonically cleaned matrix was placed in a magnetron sputtering chamber and vacuumed until the pressure was less than 1.0×10 -3 Pa, turn on the sample tray heating to keep the substrate temperature at about 150°C, then apply a -500V bias voltage to the substrate for cleaning, and the cleaning time is 20 minutes; after the sample is cleaned, pre-sputter all the target materials, and the pre-sputtering cleaning time is 10 minutes;

[0070] Preparation and deposition of Mo-S-Ti nanocomposite film, the magnetron sputtering chamber is filled with high-purity argon gas, using MoS 2 The target material (purity 99.99%) and Ti target material (purity 99.995%) are used as sputtering targets. The specific steps are as follows:

[0071] Depositing a Ti transition layer, magnetron sputtering a Ti target, heating the pre-sputtered substrate and applying a negative bias voltage, depositing a Ti transition layer on the surface of the substrate, and obtaining a Ti transition layer-deposited substrate;

[0072] The magnetron sputtering current of the Ti target is 500mA, the working gas flow rate is 40sccm, the magnetron sputtering pressure is 0.65Pa, the substrate temperature is 150℃, the substrate bias voltage is -60V, and the sputtering time is 30min;

[0073] Deposition of Mo-S-Ti nanocomposite films for MoS 2The target material and the Ti target material are magnetron sputtered simultaneously, and the substrate for depositing the Ti transition layer is heated at the same time, and a Mo-S-Ti nanocomposite layer is deposited on the surface of the Ti transition layer to obtain the Mo-S-Ti nanocomposite film;

[0074] MoS 2 The target magnetron sputtering power is 250W, the Ti target magnetron sputtering current is 110mA, the working gas flow rate is 40sccm, the magnetron sputtering pressure is 0.65Pa, the substrate temperature is 150℃, there is no bias, and the deposition time is 4.0h.

[0075] Comparative Example 2

[0076] This comparative example is a method for preparing a Mo-SC nanocomposite film without doping with Ti element, and the specific steps are as follows:

[0077] Si and W18Cr4V were selected as matrix materials, where the matrix Si was used to characterize the elemental composition and mechanical properties of the film, and the matrix W18Cr4V was used to characterize the tribological properties of the film under different test environments. The matrix materials were ultrasonically cleaned in petroleum ether and anhydrous ethanol for 20 min each, and then wiped clean with a dust-free cloth. The ultrasonically cleaned matrix was placed in a magnetron sputtering chamber and vacuumed until the pressure was less than 1.0×10 -3 Pa, turn on the sample tray heating to keep the substrate temperature at about 150°C, then apply a -500V bias voltage to the substrate for cleaning, and the cleaning time is 20 minutes; after the sample is cleaned, pre-sputter all the target materials, and the pre-sputtering cleaning time is 10 minutes;

[0078] Then, high-purity argon gas was filled into the magnetron sputtering chamber as the working gas. 2 Target (purity 99.99%), Ti target (purity 99.995%) and C target (purity 99.999%) are used as sputtering targets. The specific steps are as follows:

[0079] Depositing a Ti transition layer, magnetron sputtering a Ti target, heating the pre-sputtered substrate and applying a negative bias voltage, depositing a Ti transition layer on the surface of the substrate, and obtaining a deposited Ti transition layer substrate; the magnetron sputtering current of the Ti target is 500 mA, the working gas flow rate is 40 sccm, the magnetron sputtering pressure is 0.65 Pa, the substrate temperature is 150° C., the substrate bias voltage is -60 V, and the sputtering time is 30 min;

[0080] Deposition of Mo-SC nanocomposite film, MoS 2 The target material and the C target material are magnetron sputtered simultaneously, and the substrate for depositing the Ti transition layer is heated at the same time, and a Mo-SC nanocomposite layer is deposited on the surface of the Ti transition layer to obtain the Mo-SC nanocomposite film;

[0081] MoS 2 The magnetron sputtering power of the C target is 250 W, the working gas flow rate is 40 sccm, the magnetron sputtering pressure is 0.65 Pa, the substrate temperature is 150°C, there is no bias, and the deposition time is 4.0 h.

[0082] Comparative Example 3

[0083] This comparative example is a method for preparing a Mo-S-Ti-C nanocomposite film with varying Ti and C content. Compared with Example 2, the only difference is that the Ti and C co-doped MoS 2 When forming a nanocomposite layer, the magnetron sputtering power of the C target and the magnetron sputtering current of the Ti target are changed. The specific steps are as follows:

[0084] Si and W18Cr4V were selected as matrix materials, where the matrix Si was used to characterize the elemental composition and mechanical properties of the film, and the matrix W18Cr4V was used to characterize the tribological properties of the film under different test environments. The matrix materials were ultrasonically cleaned in petroleum ether and anhydrous ethanol for 20 min each, and then wiped clean with a dust-free cloth. The ultrasonically cleaned matrix was placed in a magnetron sputtering chamber and vacuumed until the pressure was less than 1.0×10 -3 Pa, turn on the sample tray heating to keep the substrate temperature at about 150°C, then apply a -500V bias voltage to the substrate for cleaning, and the cleaning time is 20 minutes; after the sample is cleaned, pre-sputter all the target materials, and the pre-sputtering cleaning time is 10 minutes;

[0085] Then, high-purity argon gas was filled into the magnetron sputtering chamber as the working gas. 2 Target (purity 99.99%), Ti target (purity 99.995%) and C target (purity 99.999%) are used as sputtering targets. The specific steps are as follows:

[0086] Depositing a Ti transition layer, magnetron sputtering a Ti target, heating the pre-sputtered substrate and applying a negative bias voltage, depositing a Ti transition layer on the surface of the substrate, and obtaining a deposited Ti transition layer substrate; the magnetron sputtering current of the Ti target is 500 mA, the working gas flow rate is 40 sccm, the magnetron sputtering pressure is 0.65 Pa, the substrate temperature is 150° C., the substrate bias voltage is -60 V, and the sputtering time is 30 min;

[0087] Deposition of Ti and C co-doped MoS 2 Nanocomposite layer, MoS 2 The target material, the Ti target material and the C target material are magnetron sputtered simultaneously, and the substrate for depositing the Ti transition layer is heated at the same time, and Ti and C co-doped MoS are deposited on the surface of the Ti transition layer. 2 Nanocomposite layer, to obtain the Mo-S-Ti-C nanocomposite film;

[0088] MoS 2 The target magnetron sputtering power is 250W, the C target magnetron sputtering power is 150W, the Ti target magnetron sputtering current is 400mA, the working gas flow rate is 40sccm, the sputtering pressure is 0.65Pa, the substrate temperature is 150℃, there is no bias, and the deposition time is 4.0h.

[0089] Structural characterization and performance testing

[0090] Example 1 Characterization of the cross-sectional morphology of the obtained film: A field emission scanning electron microscope (FESEM, SU8020) produced by HITACHI was used to observe the MoS 2 The surface and cross-sectional morphology of the nanocomposite film ( Figure 1 and Figure 2 Test results: The MoS 2 The surface and cross-section morphology of the nanocomposite film are dense and uniform, without defects such as pores; the thickness of the Ti transition layer is about 150nm, and the MoS 2 The thickness of the nanocomposite film is about 2.3 μm.

[0091] Example 1 Microstructure characterization of the obtained film: A transmission electron microscope (TEM, Tecnai G2 F20 S-TWIN) produced by FEI Company was used to observe the MoS 2 The microstructure of the composite film is shown in Figure 2. Figure 3 Test results: The MoS 2 The nanocomposite film is composed of amorphous Ti, C and MoS 2 Nanocrystalline composite structure, in which MoS 2 Nanocrystal size is less than 10nm.

[0092] Characterization of elemental composition of the film: The elemental composition of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 was characterized by energy dispersive X-ray spectrometer (EDS, JSM-5601LV). The results are shown in Table 1.

[0093] Table 1 Element composition of thin films (atomic percentage)

[0094]

[0095]

[0096] It can be seen from Table 1 that, under the premise that the substrates of Example 1 and Example 2 are different but the deposition parameters of the films are the same, the elemental composition of the films obtained is almost the same; by changing the film deposition parameters, a Mo-S-Ti nanocomposite film without C element doping, a Mo-SC nanocomposite film without Ti element doping, and a Mo-S-Ti-C nanocomposite film with changed Ti and C element contents were obtained.

[0097] Characterization of mechanical properties of the film: The hardness and elastic modulus of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were measured using an NHT2 nanoindenter produced by Anton Parr. In order to avoid the influence of the matrix effect on the test results, the indentation depth did not exceed 1 / 10 of the film thickness. The results are shown in Table 2.

[0098] Table 2 Nanoindentation hardness and elastic modulus of films

[0099] Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Hardness(GPa) 8.36 8.65 0.69 5.65 8.74 Elastic modulus(GPa) 95.60 97.38 27.81 68.12 115.34

[0100] It can be seen from Table 2 that the mechanical properties of Comparative Example 1 are the worst, followed by Comparative Example 2; since the matrix effect is avoided, the test results of Example 1 and Example 2 are very similar; benefiting from the maximum element doping content, Comparative Example 3 has the highest hardness and elastic modulus.

[0101] Vacuum room temperature tribological performance test of the film: Anton Parr HVTRB friction tester was used to test the vacuum room temperature tribological performance of Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3. A Φ6 mm GCr15 steel ball was selected as the friction pair, the load was 2 N, the motion mode was rotation mode, the rotation radius was 6 mm, the rotation speed was 600 rpm, and the total number of revolutions was 10,000. The pressure of the vacuum test was less than 3.0 × 10 -3 Pa, and define the film failure point when the friction coefficient exceeds 0.3. The friction curve is as follows: Figure 4 Test results: After a short running-in period, the friction coefficients of Example 2, Comparative Example 1 and Comparative Example 2 in a vacuum environment are similar, and have a low and stable friction coefficient (~0.02-0.03) within the test range. In contrast, Comparative Example 3 fails at around 40 revolutions, and has an extremely short lifespan.

[0102] Test of atmospheric normal temperature tribological properties of the film: Anton Parr HVTRB friction tester was used to test the atmospheric normal temperature tribological properties of the film for Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3. A Φ6mm GCr15 steel ball was selected as the friction pair, the load was 2N, the motion mode was the rotation mode, the rotation radius was 6mm, the rotation speed was 600rpm, and the total number of revolutions was 10,000. The atmospheric normal temperature environmental conditions were 20-25°C, 40±3%RH, and the friction coefficient was defined as exceeding 0.3, which was the failure point of the film. The friction curve was as follows Figure 5 Test results: Under normal atmospheric temperature, the friction coefficient of Example 2 is not only the most stable, but also the lowest, with an average friction coefficient of 0.093; the friction coefficient of Comparative Example 1 increases significantly, with an initial friction coefficient of about 0.2, which decreases as the experiment progresses, and is about 0.12 at the end of the experiment; the friction coefficient of Comparative Example 2 gradually increases from 0.1 at the beginning of the experiment, and with a friction coefficient of 0.3 as a reference, Comparative Example 2 fails at about 3150 revolutions, reaches 0.34 at about 3600 revolutions, and then gradually decreases to below 0.3, but the friction coefficient fluctuates greatly in the subsequent process; Comparative Example 3 fails at about 100 revolutions, and has a very short lifespan.

[0103] The tribological performance test of the film at atmospheric high temperature (500°C) was carried out on Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 using a Zhongke Kate HV-1000 high temperature friction tester. 3 N 4 The ceramic ball is used as the friction pair, with a load of 2N, a rotation mode, a rotation radius of 4mm, a rotation speed of 500rpm, and a total number of revolutions of 5000. The atmospheric high-temperature tribological performance test temperature is 500±10℃, and it is defined that the film failure point is reached when the friction coefficient exceeds 0.3. The friction curve is as follows Figure 6 Test results: Example 2, i.e., the MoS 2 The friction coefficient of the nano-composite film is the lowest and most stable in the high temperature (500℃) environment of the atmosphere, with an average friction coefficient of 0.066; Comparative Example 1 fails at around 260 revolutions and has a very short lifespan; After a short running-in period, the friction coefficient of Comparative Example 2 tends to be stable, with an average friction coefficient of 0.09; The friction coefficient of Comparative Example 3 is relatively high and fluctuates greatly, with an average friction coefficient of 0.16.

[0104] The tribological performance statistics of Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 under various environments are shown in Table 3.

[0105] Table 3 Statistics of tribological properties of films under different environments

[0106] Vacuum room temperature Normal atmospheric temperature High atmospheric temperature (500℃) Example 2 √ √ √ Comparative Example 1 √ ○ × Comparative Example 2 √ × √ Comparative Example 3 × × ○

[0107] Note: √Good○General×Invalid;

[0108] In summary, only Example 2, i.e., the MoS 2 The nanocomposite film can have good tribological properties in vacuum, normal atmospheric temperature and high temperature (500℃) environments at the same time, showing excellent environmental adaptability.

[0109] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A MoS2-based nanocomposite film, characterized in that: It comprises a Ti transition layer and a Ti and C co-doped MoS2 nanocomposite layer deposited on the surface of the Ti transition layer; in the Ti and C co-doped MoS2 nanocomposite layer, the percentage of Ti atoms is 5.0-8.0%, the percentage of C atoms is 35.0-45.0%, and the balance is MoS2.

2. The MoS2-based nanocomposite film according to claim 1, characterized in that: The thickness of the Ti transition layer is 100-300 nm; the thickness of the MoS2-based nanocomposite film is 2.0-3.0 μm.

3. The MoS2-based nanocomposite film according to claim 1 or 2, characterized in that: The hardness of the MoS2-based nanocomposite film is greater than 8.0 GPa, the elastic modulus is greater than 90.0 GPa, the average friction coefficient in vacuum is less than 0.05, the average friction coefficient in normal atmospheric temperature is less than 0.11, and the average friction coefficient in atmospheric high temperature of 500° C. is less than 0.

1.

4. The method for preparing a MoS2-based nanocomposite film according to any one of claims 1 to 3, characterized in that: The following steps are involved: Using a first argon gas as a working gas and a first Ti target material for first magnetron sputtering, while first heating the substrate and applying a negative bias voltage, a Ti transition layer is deposited on the surface of the substrate to obtain a Ti transition layer deposited substrate; the magnetron sputtering current of the first Ti target material is 400-800 mA, and the first magnetron sputtering time is 10-30 min; Using a second argon gas as the working gas, a MoS2 target, a second Ti target and a C target are simultaneously subjected to a second magnetron sputtering, and the Ti transition layer substrate is simultaneously subjected to a second heating, and a Ti and C co-doped MoS2 nanocomposite layer is deposited on the surface of the Ti transition layer to obtain the MoS2-based nanocomposite film; The magnetron sputtering power of the MoS2 target is 200-300W, the magnetron sputtering power of the C target is 200-300W, the magnetron sputtering current of the second Ti target is 80-120mA, and the time of the second magnetron sputtering is 3.5-5.0h.

5. The preparation method according to claim 4, characterized in that: The flow rate of the first argon gas is 20-40 sccm, and the pressure is 0.5-0.8 Pa; the temperature of the first heating is 100-200° C., and the negative bias voltage is -100-0V.

6. The preparation method according to claim 4, characterized in that: The flow rate of the second argon gas is 20-40 sccm, and the pressure is 0.5-0.8 Pa; the temperature of the second heating is 100-200° C., and no substrate bias is applied.

7. The preparation method according to claim 4 or 5, characterized in that: The material of the substrate includes Si, W18Cr4V, Inconel 718 or 440C.

8. The preparation method according to claim 4 or 5, characterized in that: Before the first magnetron sputtering, the method further includes sequentially performing ultrasonic cleaning and plasma cleaning on the substrate and pre-sputtering on the target material.

9. Application of the MoS2-based nanocomposite film described in any one of claims 1 to 3 or the MoS2-based nanocomposite film prepared by the preparation method described in any one of claims 5 to 8 in the surface engineering of aerospace mechanical moving parts.

10. A device, characterized in that: It comprises a substrate and a MoS2-based nanocomposite film deposited on the surface of the substrate; the MoS2-based nanocomposite film is the MoS2-based nanocomposite film described in any one of claims 1 to 3 or the MoS2-based nanocomposite film prepared by the preparation method described in any one of claims 5 to 8.

Citation Information

Patent Citations

  • Method for preparing anti-attrition MoS2 / C / Ti composite film by magnetron sputtering

    CN101654771A

  • Method for preparing wear-resistant hard film through magnetron sputtering

    CN104513956A

  • Molybdenum disulfide / tungsten disulfide multi-layer tantalum-doped thin film and preparation method and application thereof

    CN111172498A

  • Preparation method of molybdenum disulfide (MoS2) based nanocomposite film doped with Ti and C

    CN111304616A

  • Molybdenum disulfide / tungsten diboride nano-composite multilayer film and preparation method and application thereof

    CN117187764A